Offline Signature Verification Using Various Methods: A Review (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Offline signature verification was the first approach to be applied for  solving the signature verification problem. It involves the discrimination of genuine and forged signatures on static images.  Unlike online systems, offline systems have only the static image  containing the signature as an input, without having any knowledge on  the signing process. Some difficulties that may arise in offline systems  are related to the scanning process (noise on the image) and to the  signature acquisition process where different pen tips and widths can  produce different shapes. This paper presents a brief study on offline  signature verification and recognition using various methods, FAR and  FRR is calculated for each method and results are compared.
Keywords: DCT; FAR; FRR; signature verification, features; PMT